Comparison of four histological scoring systems for autoimmune hepatitis to improve diagnostic sensitivity - Soomin Ahn; Sook-Hyang Jeong; Eun Ju Cho; Kyoungbun Lee; Gilhyang Kim; Haeryoung Kim (Clinical and Molecular Hepatology, 2024)
Background/Aims The histological criteria in the 1999 and 2008 scoring systems proposed by the International Autoimmune Hepatitis Group (IAIHG) have their inherent limitations in diagnosing autoimmune hepatitis (AIH). In this study, we evaluated the histology components of four scoring systems (1. revised original scoring system [“1999 IAIHG”], 2. simplified scoring system [“2008 IAIHG”], 3. modified histologic criteria [“2017 UCSF”], and 4. a new histologic criteria proposed by the International AIH Pathology Group [“2022 IAHPG”]) in AIH patients. Methods Medical records and liver biopsies were retrospectively reviewed for 68 patients from two independent medical institutions, diagnosed with AIH based on the 1999 IAIHG system between 2006 and 2016. The histological features were reviewed in detail, and the four histological scoring systems were compared. Results Out of the 68 patients, 56 (82.4%) patients met the “probable” or “definite” AIH criteria of the 2008 IAIHG system, and the proportion of histologic score 2 (maximum) was 40/68 (58.8%). By applying the 2017 UCSF criteria, the number of histology score 2 increased to 60/68 (88.2%), and “probable” or “definite” AIH cases increased to 61/68 (89.7%). Finally, applying the 2022 IAHPG histology score resulted in the highest number of cases with histologic score 2 (64/68; 94.1%) and with a diagnosis of “probable” or “definite” AIH (62/68; 91.2%). Conclusions The recently proposed UCSF/IAHPG histological criteria increased the histology score of AIH. Substituting the histology component of the 2008 IAIHG system with the 2022 IAHPG criteria increased the sensitivity for diagnosing AIH (≥“Probable AIH”) from 82.4% to 91.2%.